The Influence of Service Quality and Product Quality Through Customer Satisfaction on Customer Loyalty at Vegetarian Restaurant Fortunate Taste Batam - Theresia Pradiani; Suwandi; Fathorrahman (Universitas Pendidikan Ganesha, 2023)
As the growth of the culinary business, especially in Vegetarian food service providers, significantly increased in the city of Batam, the increase in visitors to the Fortunate Taste Vegetarian Batam restaurant was also quite large. The purpose of this study was to analyze the effect of service quality and product quality on customer satisfaction, the effect of service quality, product quality, and customer satisfaction on customer loyalty, and to prove that customer satisfaction was able to mediate the effect of service quality and product quality on customer loyalty. The population of this research was the customers of Fortunate Taste Vegetarian Restaurant. Total of sample was 100 respondents with a purposive sampling technique. The results showed that service quality and product quality had a positive and significant effect on customer satisfaction, service quality had a positive and insignificant effect on customer loyalty, product quality had a positive and significant effect on customer loyalty, and customer satisfaction had a negative and insignificant effect on customer loyalty. Customer satisfaction was not proven to act as an intervening variable to mediate the effect of service quality and product quality on customer loyalty. The implication of this research is that the management of Fortunate Taste Vegetarian restaurant in Batam needs to improve service quality and product quality to meet customer expectations and satisfaction in order to increase customer loyalty.